Sistem Pendukung Keputusan Penerimaan Beasiswa Bagi Siswa Kurang Mampu Dengan Menggunakan Metode Profile Matching - Alwendi Alwendi; Yusra Fadillah (Prosiding SISFOTEK, 2020)
The scholarship selection process at Padangsidimpuan 4 High School has many obstacles in the decision making process. This is because there is no objective method that can decide quickly and accurately. To assist in determining who is eligible to receive a scholarship, this study will use the DSS (Decision Support System) with the Multi Criteria Decision Making model. The method used is the Profile Matching method. The Profile Matching method was chosen because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is the one who is entitled to receive a scholarship based on specified criteria. The study was conducted by finding the weight value for each sub-aspect, then the ranking process was carried out which would determine the optimal alternative, namely the best students who would be considered by decision makers to get a scholarship.